A universal soil classification system from the perspective of the General Theory of Classification: a review - Nikiforova, Aleksandra Aleksandrovna; Fleis, Maria E. (Bulletin of Geography. Physical Geography Series, 2018)
The paper addresses issues of the application of the General Theory of Classification in the development of a universal soil classification system. Requirements for such a system, the comparison of different approaches to its development, and obstacles on the way to it are outlined. Besides, the problem of the definition of soils and importance of distinguishing between differentiating and diagnostic criteria are discussed. It is shown that, from the perspective of the General Theory of Classification, a universal soil classification system should be natural, genetic, “fundamental-and-specific”, and hierarchical. It is concluded that the World Reference Base for Soil Resources (WRB) does not meet these requirements and therefore cannot be considered as universal. The ways of addressing the problems of a universal soil classification system are suggested.